2001
DOI: 10.1002/1521-3765(20011015)7:20<4465::aid-chem4465>3.0.co;2-w
|View full text |Cite
|
Sign up to set email alerts
|

Development of Dirhodium(II)-Catalyzed Generation and Enantioselective 1,3-Dipolar Cycloaddition of Carbonyl Ylides

Abstract: Catalytic, enantioselective, tandem carbonyl ylide formation/cycloaddition of 2-diazo-3,6-diketoester 2 with the use of dirhodium tetrakiscarboxylate and tetrakisbinaphtholphosphate catalysts to give the cycloadducts 3 in good yields and up to 90% ee is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(30 citation statements)
references
References 86 publications
1
29
0
Order By: Relevance
“…The main classes of these are detailed below. [27][28][29][30] reported the preparation of a new chiral dirhodium carboxylate complexes derived from Lproline (2)(3)(4)(5)(6)(7)(8)(9). The catalysts were prepared by ligand exchange in which the sodium salts of rhodium carbonates were exchanged with the appropriate N-substituted-sulphonyl-L-prolinate ligand (Fig.…”
Section: Dirhodium Carboxylate Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The main classes of these are detailed below. [27][28][29][30] reported the preparation of a new chiral dirhodium carboxylate complexes derived from Lproline (2)(3)(4)(5)(6)(7)(8)(9). The catalysts were prepared by ligand exchange in which the sodium salts of rhodium carbonates were exchanged with the appropriate N-substituted-sulphonyl-L-prolinate ligand (Fig.…”
Section: Dirhodium Carboxylate Complexesmentioning
confidence: 99%
“…The complex activity has been examined for asymmetric cyclopropanation of alkenes with vinyl and phenyl-diazoester giving a high enantioselectivities up to 92% [36]. In 2001, Hodgson et al [7] reported the preparation of two analogues of the McKervey and Betrilsson catalysts by applying the Callot method [35]. Again, the catalysts were fully characterized by NMR, Mass spectrometery, and CHNS analysis.…”
Section: A Mckervey Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Their remarkable selectivity has reached a stage where they can function as a powerful tool in building up value added molecules with complex structures [7,[15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%
“…This immense interest originates from their exceptional ability to effectively catalyze a broad spectrum of reactions with high levels of chemo-, regio-and stereo-selectivity. These transformations involve aziridinations [16][17][18], C-H insertions [7,19,20], ylide transformations [21][22][23][24][25], Lewis acid-promoted reactions [21,[26][27][28][29][30], cross-coupling reactions [31], cyclopropanation and cyclopropenation reactions [32][33][34][35]. In fact, they have proven their potential, particularly, in the field of asymmetric synthesis.…”
Section: Introductionmentioning
confidence: 99%